A Macroprudential Framework for Monitoring and Examining Financial Soundness - Jose Ramon G. Albert; Lotte Schou-Zibell; Lei Lei Song (Philippine Institute for Development Studies (PIDS), 2012)
This paper describes concepts and tools behind macroprudential monitoring and the growing importance of macroprudential tools for assessing the stability of financial systems. This paper also employs a macroprudential approach in examining financial soundness and identifying its determinants. Using data from selected developing economies in Asia, South America, and Europe as well as selected economies from the developed world, panel regressions are estimated to quantify the impacts of the major influences on key financial soundness indicators, including capital adequacy, asset quality, and earnings and profitability.
Keywords: E44; E58; E65; G21; G28; 330; early warning system; banking regulation; macroprudential; banks; banking crises; banking supervision; stress testing